Model Based Markerless 3D Tracking applied to Augmented Reality - Lima, Joao Paulo Silva do Monte; Simoes, Francisco Paulo Magalhaes; Figueiredo, Lucas Silva; Kelner, Judith (Journal on Interactive Systems, 2010)
This paper presents the implementation of 3D tracking techniques based on natural features for augmented reality. The contemplated techniques are from the model based category, comprising recursive and non-recursive methods, as well as edge and texture based techniques. An evaluation of the implemented 3D trackers was performed regarding performance and accuracy under different scenarios.